Optimal efficiency point membership incorporating fuzzy logic and automatic control of various charging stages for electric vehicles - Wang, Xinyan; Li, Yichao (Frontiers in Mechanical Engineering, 2024)
Currently, electric vehicle technology is an emerging renewable energy technology. However, the wireless charging system of electric vehicles is a major challenge in this field. How to achieve intelligent charging and track the optimal efficiency point is extremely important. Therefore, the research will combine the wireless charging system of electric vehicles and fuzzy logic algorithms to explore this problem. The optimal efficiency point membership integrating fuzzy logic and the automatic control system for the automotive charging stage is proposed. The model achieves dynamic tracking and adaptive control of the optimal efficiency point by analyzing the characteristics of the static wireless charging system of electric vehicles. The system adopts primary side phase-shifting control and secondary side controllable rectifier regulation, combined with optimized fuzzy control algorithm. The experimental results showed that when the secondary coil was stable, the duty cycle was stable at around 75.6%, and the current was stable at 5A. When the mutual inductance values were 10uH, 15uH, and 20uH, the efficiency of the primary coil before control decreased with the increase of resistance. This system has good applicability and feasibility for controlling electric vehicle charging and tracking optimal efficiency points.